Human resource management practices, service innovation, organizational commitment and organizational performance among educational institutions in Pakistan - Nawal, Ayesha; Universiti Sultan Zainal Abidin . Faculty of Business and Management (2021)
Private educational institutions gained popularity at higher secondary level based on the perception of offering better services to the students who are keenly concerned about their academic and professional careers. However, these institutions are criticized for their deteriorating performance and lack of conformance to the quality standards of education. These institutions undergo poor performance because of inadequate implementation of human resource management practices to enhance the human assets' aptitude and capability. Majority of teaching faculty have lack of competence and commitment to put efforts for the accomplishment of organizational objectives. Under- taffing, lack of professional trainings and staff incompatibility with emerging technological trends are among reasons to lower the performance of institutions. However, empirical study that examine the inter-relationship of human resource
management practices, service innovation, organizational commitment, and organizational performance simultaneously in a single model has not been conducted at private higher secondary educational institutions of Pakistan. This study intends to examine th inter-relationship among constructs leading to better organizational performance. Objective of this study was to examine the influence of human resource management practices on the performance of private higher secondary educational institutions of Punjab, Pakistan. This study also aimed to examine the effect of human resource management practices on service innovation and organizational commitment and their subsequent effect on the performance of private higher secondary educational institutions of Punjab Paki tan. Finally, study aimed to examine the mediational role of service irmovation and organizational commitment on the relationship between
human resource management practices and organizational performance. This study was deductive, explanatory in nature and cross-sectional in terms of time horizon. Target population of study comprised on staff working in private higher secondary educational institutions of Punjab, Pakistan. Sampling frame was developed, and structured questionnaires were distributed face-to-face to collect quantitative data. From total collected questionnaires, 372 responses were selected through random sampling method and data was analysed using SPSS (25.0) and AMOS (25.0) software. Findings of this study revealed that human resource management practices have significant positive influence on service irmovation and organizational commitment. Subsequently, service irmovation and organizational commitment have positive effect on organizational performance. However, the direct effect of human resource management practices on organizational performance was not significant. Thus, service irmovation and organizational commitment fully mediate the relationship between human resource management practices and organizational performance. This study offered significant theoretical insights as this study was pioneer to demonstrate an integrated structural model that links human resource management practices, service innovation, organizational commitment, and organizational performance in higher secondary educational context. Practically, this study is significant for owners and managers of private educational institutions by predicting the influential factors to improve performance. Implementation of human resource management practices lead to enhance staff commitment and service innovation capabilities that consequently improve overall performance of institutions.
1. Introduction -- 2. Literature review -- 3. Methodology -- 4. Data analysis and findings -- 5. Discussion and conclusions
Thesis (Degree of Doctor of Philosophy) - Universiti Sultan Zainal Abidin, 2021
Includes bibliographical references (leaves 402-486)
Keywords: Universiti Sultan Zainal Abidin -- Dissertations; Universiti Sultan Zainal Abidin -- Faculty of Business and Management -- Dissertations; Dissertations, Academic; Organizational behavior; Organizational behavior -- Pakistan; Personnel management